UPAYA PENANGANAN TUBERKULOSIS PARU PADA PASIEN LAKI-LAKI USIA 48 TAHUN MELALUI PENDEKATAN KEDOKTERAN KELUARGA DI PUSKESMAS BANDA BARO KABUPATEN ACEH UTARA - Muhammad Nawawi Chaniago (Jurnal Medika Hutama, 2026)
Mr. P came to the Banda Baro Community Health Center with a primary complaint of coughing up blood for approximately one month. The cough initially began approximately two months ago, producing productive, yellowish-white sputum, and was frequent, especially at night. Over the past month, the cough has been accompanied by fresh red blood mixed with sputum, in small to moderate amounts, without clots, and without vomiting. Primary data was obtained through a self-anamnesis and physical examination, including home visits, family folders, and patient files. The assessment was based on a holistic diagnosis at the beginning, during, and at the end of the visit, using quantitative and qualitative methods. Interventions included educating the family about pulmonary TB, lifestyle modifications, and disease management, and explaining potential complications of the disease, encouraging regular treatment and preventive measures.